Status of Antiviral Agents in Treatment of COVID-19 - Shahani, Savita R. (International Journal of Pharmaceutical & Biological Archive, 2021)
Severe acute respiratory syndrome coronavirus-2 is responsible for COVID-19, a novel disease which was first identified in city of Wuhan in China. The World Health Organization declared official name of the disease as COVID-19. Due to presence of spike glycoproteins on its envelope, it was named as a coronavirus. Promising drug targets for anti-COVID activity include non-structural proteins such as 3-chymotrypsin-like protease, papain-like protease, and RNA-dependent RNA polymerase. Additional drug target includes viral entry. Various drugs which are tested for COVID-19 infection are described here with their present status: (1) Lopinavir–ritonavir-Both the drugs are protease inhibitors and are given as combination therapy currently none of the guidelines recommend Lopinavir–ritonavir for the treatment of COVID-19, as clinical trials have not demonstrated its benefit in COVID-19. (2) Favipiravir (FPV)-It is a broad-spectrum antiviral drug which acts by inhibiting viral RNA-dependent RNA polymerase. None of the organizational guidelines recommend using FPV in the management of COVID-19, due to varying results of existing clinical trials data. (3) Remipiravir (REM)-It is also a broad-spectrum antiviral drug which acts by inhibiting viral RNA-dependent RNA polymerase. United States Food and Drug Administration has approved the REM for the treatment of COVID-19 in adults and children above 12 years in hospitalized COVID-19 patient. Drug Controller General of India has granted approval to REM for restricted emergency use for the treatment of COVID-19 but guidelines for the management of COVID-19 among children issued by the government of India mentions that there are insufficient data regarding safety and efficacy of REM in children below 18 years of age. The WHO has issued a conditional recommendation against the use of REM in hospitalized patients, regardless of disease severity, due to insufficient evidence that REM improves survival and other outcomes in these patients. Some of the newer antiviral drugs are in various phases of clinical trials for the treatment of COVID-19. How these potential COVID-19 treatments will translate to effective therapy in human is difficult to predict.